Home and Diasporic Imagination: Incorporating Immigrant Writer Chang Shi-Kuo in (Chinese) American Literary Studies - Huang, East Carolina University, USA, Su-ching (Asiatic: IIUM Journal of English Language and Literature, 2015)
As part of a larger project aiming to include Sinophone US literature in US literary studies, this essay focuses on the Taiwan immigrant writer Chang Shi-Kuo‘s work and his recurrent themes, such as the obsession with China, the anxiety over patrilineal transmission, male hysteria and racial melancholia. The thematic concerns and stylistic experimentalism in Chang‘s fiction intersect with those of other ethnic Chinese writers in the US, whether they write in Chinese or English. Focusing on Chang‘s fiction and its engagement of the diasporic imagination with the aforementioned themes, this paper examines Chang‘s portrayals of US and Taiwan/Chinese societies. While his characters‘ US experience often suggests a critique of technocracy and commercialism, and the ensuing interpersonal alienation in the US, his depiction of Taiwan seems more nuanced and sanguine. I propose to read the discrepancy between such portrayals as resulting more from diasporic nostalgia than from lived experience. Despite Chang‘s explicit attachment to Taiwan, he is also quite aware of his immigrant status. Observing the transition of student immigrants into US citizens, he rejects the label of ―Overseas Student literature; instead, he contends that student immigrant literature will gradually become the literature of the adopted country. Chang‘s affinity with US-born Chinese American writers can be observed in his Chinese protagonists‘ male hysteria, which hints at the dissolution of traditional Chinese gender division in North America. The inability to sustain a traditional Chinese family in North America suggests a failure to ensure a profitable future for the Chinese diaspora, which I describe as anxiety over patrilineal transmission, after the Asian American critic Sau-ling Wong. Such male hysteria not only harks back to the ―obsession with China‖ but also points to an affinitybetween Sinophone US literature and Chinese American literature written in English by US-born Chinese American writers.